Self -reported bruxism in patients undergoing Orthodontic treatment – a cross-sectional study - Munnal Gulzar; Mubassar Fida; Rashna Hoshang Sukhia (BMC Oral Health)
Abstract Background Orthodontic treatment involves manipulation of tooth position that can temporarily lead to occlusal interferences capable of inducing bruxism. The objectives of this study were to determine the self-reported incidence of bruxism and its association with factors such as facial type, divergence, skeletal and dental malocclusions in orthodontic patients. Materials and methods 80 patients who underwent a minimum of six months of orthodontic treatment were surveyed using a validated self-reported bruxism questionnaire for the presence or absence of bruxism. Data regarding patients’ facial type, divergence, skeletal and dental malocclusions were measured and collected from the patients’ orthodontic records. Binomial logistic regression analysis was used to assess the association of these factors with bruxism. Results About 45% of the orthodontic patients reported bruxism after the commencement of orthodontic treatment. The median age of the sample was 19.8 (17.7, 24.3) years and 60% of them were women. Binomial logistic regression analysis showed an insignificant association of gender and age with bruxism. When analyzing the association with facial type, divergence, skeletal and dental malocclusion no statistically significant association was found. However, patients with hypodivergent face [odds ratio (OR) = 2.4; 95% confidence interval (CI) = 0.7–8.5] and dental class III [OR = 4.0; 95% CI = 0.3–51.0] were more likely to report bruxism after the initiation of orthodontic treatment. A statistically significant association was found with jaw fatigue or soreness upon awakening (28.7%), clenching (27.5%) and grinding (25%) in the bruxism group (p-value ≤ 0.001). Teeth and gum soreness were also significantly associated with bruxism, affecting 25% of the orthodontic patients (p-value ≤ 0.001). On the contrary, nocturnal grinding (10%) and temporal headaches (21.3%) were negatively correlated with bruxism. Conclusions There is a risk of bruxism among orthodontic patients, with 45% of them reporting bruxism following the initiation of treatment. Patients with bruxism commonly reported jaw fatigue or soreness upon awakening, clenching, grinding, teeth and gum soreness. Factors such as facial type, facial divergence, skeletal and dental malocclusions have no impact on the onset of bruxism during orthodontic treatment.